A Case of Uterine Lymphangioleiomyomatosis Complicated by Tuberous Sclerosis Complex - Kaori Yamada; Yukio Yamanishi; Junichi Aratake; Nanayo Sasagasako; Yoshihide Inayama; Rei Gou; Atsuko Kawamura; Megumi Yamanishi; Kenzo Kosaka (Case Reports in Obstetrics and Gynecology)
Lymphangioleiomyomatosis (LAM) is one of the presentations of perivascular epithelioid cell neoplasm that is frequently complicated by tuberous sclerosis complex (TSC). Here, we report an uncommon case of uterine LAM treated with everolimus, which is a mechanistic target of rapamycin (mTOR) inhibitor. A 42-year-old female patient (gravida 0) with a history of TSC presented with abdominal pain. Pelvic magnetic resonance imaging showed multiple masses in the uterine myometrium, suggesting tumors that may contain internal hemorrhagic components. The lesions were suspected as the root cause of her symptoms. After everolimus was administered for a previously diagnosed renal angiolipoma, her uterine tumors temporarily decreased in size. Subsequently, laparoscopic hysterectomy and bilateral salpingectomy were performed since she could not tolerate everolimus for a long period due to the medication’s side effects. Furthermore, the patient was diagnosed with LAM through histopathological examination after surgical resection. Therefore, it is advisable to suspect and investigate uterine LAM when a patient with a history of TSC presents with irregular genital bleeding or abdominal pain. Moreover, mTOR inhibitors may be a treatment option, in addition to surgery, in cases of uterine LAM exacerbation.